2005
DOI: 10.1111/j.1743-7563.2005.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of abnormal Papanicolaou smears and cytohistological correlation: A study from Aga Khan University Hospital, Pakistan

Abstract: Objectives: To determine the prevalence of abnormal Papanicolaou (Pap) smears in patients visiting the gynecologic outpatient department at Aga Khan University Hospital, Karachi (AKUH) and their cytohistologic correlation. This data was also compared with other international institutions. Methods: A database search of all abnormal cervical cytological cases diagnosed in the gynecologic outpatient department at Aga Khan University Hospital in the last 10 years (i.e. from 1994 to 2004), as well as their follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 9 publications
5
9
2
Order By: Relevance
“…(Table 2) Concordant 38 76 Table 50 100 In the present study, the overall concordance rate was 76%which is comparable to other studies e.g. Study by Nawaz [6] (a study from Aga Khan University, Pakistan) where the concordance rate was74%. The other studies like Saha"s [7], Yeoh [8] & Rasbridge [9] has concordance rates as 60%, 52% and 81.2% respectively (Table 3).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…(Table 2) Concordant 38 76 Table 50 100 In the present study, the overall concordance rate was 76%which is comparable to other studies e.g. Study by Nawaz [6] (a study from Aga Khan University, Pakistan) where the concordance rate was74%. The other studies like Saha"s [7], Yeoh [8] & Rasbridge [9] has concordance rates as 60%, 52% and 81.2% respectively (Table 3).…”
Section: Resultssupporting
confidence: 84%
“…The study by Nawaz [6]showed overall concordance rate of 74%. A total 8 numbers of cases were discrepant.…”
Section: Resultsmentioning
confidence: 94%
“…20,21 As shown in Table 2, Nawaz et al (2005) showed 74% correlation while Rasbridge et al (2005) showed 81.2% correlation between cytology and biopsy in their study which was 57% in the present study and which was increased to 92.8% within one degree of histopathological abnormality. 22,23 The overall accuracy of Pap smear reporting was 84.6% by Naik et al whereas the present study showed 82.1% accuracy. 18 Nevertheless relatively low correlation of accepted, histologically specific cytologic classification with the biopsy diagnoses is disappointing and raising some question as to the reliability of the very specific cytologic diagnosis is borderline lesions.…”
Section: Resultscontrasting
confidence: 45%
“…[9][10][11] Concordance rate for SCC [ Figure 3(b)] in our study was 88.89 % as compared to 100% concordance rate reported by Saha et al, 97.33% by Nawaz et al and 60% by Yeoh et al 9,10,12 In our study, the overall sensitivity of pap smear was 86.61%; specificity was 73.33%, PPV was 96.49 %, NPV was 39.29% and diagnostic accuracy was 85.21%. The diagnostic accuracy in our study was comparable to Naik (Table 5).…”
Section: Cyto-histological Correlationmentioning
confidence: 99%